PEMBANGGUNAN PERKEBUNAN KELAPA SAWIT DI KABUPATEN PELALAWAN TAHUN 2010-2012 - ", Abdurrahman; Anwar, Khairul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study aimed to describe the role of local government in promotingdevelopment in the field of oil palm . The usefulness of this study is for informationabout the interaction of the crucial factors and determine the dominant factors thataffect the implementation of government policy in increasing investment in oil palm .The method used in this study is qualitative methods of data that can not be expressedin terms of numbers but in the form of an explanation that describes the shape of thestate , a process , a particular event . The technique of collecting data using interviewsand documentation techniques .From the research it can be concluded that the implementation of governmentpolicy in promoting investment in palm oil have a positive impact for the region ,where investment will increase economic growth and create new job opportunities forthe community , especially the local community . In addition to the steps - steps takenby the Government of intensive Pelalawan both in terms of rules and procedures thatincreasingly facilitated and preparation of supporting infrastructure such as roads andbridges , electricity and other government Pelalawan also always strive to promote thepotential that exists territory in order interested investors to come and invest intoPelalawanKeywords : Development , Policies , Investment